High Technology Industries and Non-Union Establishments in Britain - Beaumont, P.B.; Harris, R.I.D. (Relations industrielles / Industrial Relations, 1988)
This paper seeks to remedy some existing research deficiencies in Britain where discussions of the high technology non-union relationship have overwhelmingly consisted of small partial studies of the electronics industry.